Bat Assemblage in an Oil Palm Plantation from the Colombian Llanos Foothills - Alejandra Maria Cely-Gomez,; Dennis Castillo-Figueroa,; Jairo Perez, (Tropical Life Sciences Research, 2021)
The surge of oil palm production in the Neotropics has become a major concern about the potential impacts on biodiversity. In the Colombian Orinoquia, which has shown a massive landscape transformation due to the growth of oil palm plantations, the effects of oil palm agriculture on bats in this region have not been studied up to date. To understand the impact of habitat conversion on bat diversity, we characterized bat assemblages in secondary forest and palm plantations in the Colombian Piedmont foothills (Meta, Colombia). We captured 393 individuals (forest = 81, plantation = 312) of 18 species and three families. The forest cover presented three exclusive species while the plantation had five. Species diversity (q1) and evenness (J’) were higher in the forest compared to the plantation. These differences derived from the increase in abundances of generalist species (Artibeus sp., Carollia spp.) in the plantation. Despite the habitat simplification caused by oil palm plantations, this monoculture provides a cover that is used by some bats, decreasing their risk of predation and allowing movement between patches of forest habitat as stepping-stones. Maintaining forest cover in agricultural landscapes favors diversity by generating a “spillover effect” of the forest towards plantations, which in the case of some bats contributes to the reduction of species isolation and the maintenance of ecosystem services provided by them. It is important to improve management practices of oil palm plantations to minimize negative impacts on biodiversity, considering the expansion of this productive system and the scarcity of protected areas in this region.